2021
DOI: 10.1002/dc.24735
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of solid tumors in infants by fine‐needle aspiration cytology: 5 years retrospective study from a tertiary care oncology center in South India

Abstract: Introduction Neuroblastoma (NB), Wilms tumor (WT), hepatoblastoma (HBL), germ cell tumors (GCT), rhabdomyosarcoma (RMS), and so forth are the commonly identified solid tumors in infants. Invasive diagnostic techniques are more challenging in infants than older children. fine needle aspiration cytology (FNAC) is a safe, minimally invasive and outpatient procedure which is time and cost‐effective for solid tumor diagnosis. This study aims to evaluate the role of FNAC in the diagnosis of various infantile solid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…With the advancement of modern pathology, some cases that are difficult to diagnose morphologically can be determined in combination with immunophenotyping and genetic features. It is not uncommon in clinical practice to make a diagnosis of RMS by FNAC ( 23 , 24 ), but only a few studies have discussed the cytologic diagnosis of metastatic ARMS in lymph nodes. Those three cases had been reported arising from the nasal cavity, paranasal sinus, or nasal vestibule with metastasis to cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of modern pathology, some cases that are difficult to diagnose morphologically can be determined in combination with immunophenotyping and genetic features. It is not uncommon in clinical practice to make a diagnosis of RMS by FNAC ( 23 , 24 ), but only a few studies have discussed the cytologic diagnosis of metastatic ARMS in lymph nodes. Those three cases had been reported arising from the nasal cavity, paranasal sinus, or nasal vestibule with metastasis to cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…[10] FNAC had an excellent concordance rate with histological grading in soft tissue sar-comas. The study [11] showed that FNAC helps assess tumor aggressiveness and make treatment plans. While FNAC has been examined extensively in other areas, there is a shortage of studies examining its potential impact in the Indian state of Bhilai.…”
Section: Introductionmentioning
confidence: 99%